PAUL'S PRE-CHRISTIAN ZEALOT ASSOCIATIONS: A RE-EXAMINATION OF GAL 1.14 AND ACTS 22.3 - Fairchild, Mark R. (New Testament studies, 1999)
The article explores Gal 1.14 and Acts 22.3, two statements where Paul is said to be a ζηλωτη´ς. The term is a noun, meaning ‘Zealot’. However, interpreters and commentators have always interpreted the term as an adjective, meaning ‘zealous’. By understanding Paul's statement as an adjective, interpreters and commentators have dissociated Paul from the Zealot movement which was emerging during this period of time within Judaism. However, Paul appears in these passages to claim that the Zealot movement was a powerful influence upon his formative Jewish life and theology and was a motivating factor in his persecution of the Christians. This article proposes that we seriously consider Zealot influences in the formative years of Paul.